Cutibacterium acnes Osteomyelitis 2 Years After Intra-Articular Steroid Injection - Talal Alomar; Ronnie Otieno; Sammy Alomar; Andree Jones (Annals of Internal Medicine: Clinical Cases)
We present a rare case of a patient who developed shoulder pain 2 years after intra-articular steroid injections and was diagnosed with Cutibacterium acnes osteomyelitis. Upon review of the literature, this represents one of the few documented instances of C acnes osteomyelitis in the absence of invasive surgical procedures. We intend to bring awareness and raise clinician suspicion of this condition, and we hope it can lead to more rapid diagnosis in the future.